Affect and Cognition in Managerial Decision Making: A Systematic Literature Review of Neuroscience Evidence - Cristofaro, Matteo; Giardino, Pier Luigi; Malizia, Andrea P.; Mastrogiorgio, Antonio (Frontiers in Psychology, 2022)
How do affect and cognition interact in managerial decision making? Over the last decades, scholars have investigated how managers make decisions. However, what remains largely unknown is the interplay of affective states and cognition during the decision-making process. We offer a systematization of the contributions produced on the role of affect and cognition in managerial decision making by considering the recent cross-fertilization of management studies with the neuroscience domain. We implement a Systematic Literature Review of 23 selected contributions dealing with the role of affect and cognition in managerial decisions that adopted neuroscience techniques/points of view. Collected papers have been analyzed by considering the so-called reflexive (X-) and reflective (C-) systems in social cognitive neuroscience and the type of decisions investigated in the literature. Results obtained help to support an emerging “unified” mind processing theory for which the two systems of our mind are not in conflict and for which affective states have a driving role towards cognition. A research agenda for future studies is provided to scholars who are interested in advancing the investigation of affect and cognition in managerial decision making, also through neuroscience techniques – with the consideration that these works should be at the service of the behavioral strategy field.